Long-term effect of magnesium and iron nanoparticles on solute transport in saturated condition. Issue 10 (24th August 2022) - Daraei, Elahe; Bayat, Hossein; Zamani, Pouya; Gregory, Andrew S.
ABSTRACT: The aim of this study was to investigate the long-term effect of magnesium and iron nanoparticles on solute transport and its parameters, which has not been investigated to date. Different concentrations of two types of nanoparticle metal oxides, MgO and Fe3 O4, were mixed with a loamy soil and their effects on solute transport and its parameters after three years were investigated. Nanoparticles improved soil structure through increased macro pores compared to the control, by 2.3% in the 3% concentration of MgO to 15.3% in the 3% concentration of Fe3 O4 . Immobile water content of the soil decreased from 0.42 in the control to 0.05–0.24 cm 3 cm −3 in the treatments. The mass transfer coefficient was decreased from 0.48 in the control to 0.005–0.37 in the nanoparticle treatments. Moreover, nanoparticles increased the breakthrough curve peak concentration and decreased discharge time of chloride in the extract from 0.41 and 88.8 min in the control to 0.62–0.76 and 24.7–87.9 min in the treatments, respectively. The results of this study showed that the nanoparticles affected the solute transport and its parameters in the soil. Therefore, nanoparticles could be used to simplify the nutrients transport and leaching of salt and contaminants.